068 Integrating guidelines into local clinical practice and policy using hospital-based health technology assessment. (15th August 2013) - Mitchell, M; Leas, B; Lavenberg, J; Williams, K; Umscheid, C
Abstract : Background: Most existing centres for health technology assessment (HTA) are associated with payers or government agencies, and review and analyse emerging and costly technologies. Yet, such centres can exist within individual medical centres as well, and can use HTA methods locally to synthesise, disseminate and implement best clinical practices to improve the quality, safety and value of patient care. Objectives: Describe the structure, processes and outcomes of a model of hospital-based HTA (HB-HTA) in the US, such that it can be applied elsewhere. Methods: Our academic medical centre established the centre for Evidence-based Practice (CEP) in 2006. CEP synthesises guidelines and studies for clinical and administrative leaders to inform decision-making, integrates select syntheses into practice through clinical decision support (CDS), and provides education in evidence-based practice. Local utilisation and cost data are incorporated where appropriate. Results: Nearly 200 evidence reports have been completed to date, and over 35 reports have been integrated into CDS. The median time from project opening to first draft is 4 weeks. CEP also contracts with external organisations such as the CDC and AHRQ on systematic reviews and guidelines. Discussion: To complete reviews rapidly, we work closely with requestors to define the questions up front and limit the scope, use experienced analysts to perform high yield searches with single study reviews and extraction, and use best available evidence and existing guidelines and reviews. Implications for Guideline Developers/Users: An HB-HTA centre can develop, adapt and implement guidelines locally to support a culture of evidence-based practice and decision-making.